323 Systemic administration of ladiratuzumab vedotin alone or in combination with pembrolizumab results in significant immune activation in the tumor microenvironment in metastatic breast cancer patients. (9th November 2020) - Pusztai, Lajos; Lu, Hailing; Hale, Christopher; Grosse-Wilde, Anne; Specht, Jennifer; Modi, Shanu; Han, Hyo; Cortes, Javier; Oliveira, Mafalda; Garfin, Phillip; Wang, Zejing; Onsum, Matthew
Abstract : Background: Ladiratuzumab vedotin (LV) is an investigational antibody-drug conjugate (ADC) composed of a humanized anti-LIV-1 IgG1 conjugated with monomethyl auristatin E (MMAE), a microtubule-disrupting agent. LV targets LIV-1, a protein expressed by various cancers. Along with a cytotoxic effect, LV has been shown to induce immunogenic cell death (ICD) in preclinical studies. LV is currently being investigated as a monotherapy and in combination with pembrolizumab in patients with metastatic breast cancer and other solid tumors. This correlative biomarker study aims to assess the ability of LV to modulate the tumor microenvironment (TME) in breast cancer patients. Methods: In the SGNLVA-001 trial, metastatic breast cancer patients, predominantly of the triple negative subtype (TNBC), received LV monotherapy (2.0 or 2.5 mg/kg, every 3 weeks [q3w]). In the SGNLVA-002 trial, patients with metastatic TNBC received LV (2.0 or 2.5 mg/kg, q3w) plus pembrolizumab (200 mg, q3w). To investigate the potential effect of LV or LV plus pembrolizumab on the TME, paired pre-treatment and on-treatment tumor biopsies (Cycle [C] 1 Day [D] 5 or C1D15) were collected and analyzed by RNAseq and immunohistochemistry (IHC) staining. Results: Gene expression analysis of paired biopsy TNBC samples (n=59; baseline and C1D5) showed that LV monotherapy treatment significantly induces immune response-related gene expression, MHC, co-stimulatory molecules, and PD-L1. Gene set enrichment analysis (GSEA) demonstrated enrichment of macrophage and tumor inflammation signature genes, supporting the induction of ICD and enhancement of innate immune response. Paired tumor samples from subjects treated with LV plus pembrolizumab (n=16; baseline and C1D15) showed a broader range of gene expression changes on RNAseq compared to LV monotherapy. GSEA evidenced enrichment of genes associated with cytotoxic CD8 T cells, CD4 T helper cells, dendritic cells, and macrophages, further demonstrating the induction of ICD and activation of an innate immune response. Importantly, the combination had a unique adaptive immune response induction signature. IHC analysis confirmed the increased infiltration of macrophages after LV monotherapy. The combination with pembrolizumab resulted in a further increase in macrophages and a prominent influx of CD8 T cells. Conclusions: Systemic administration of LV monotherapy resulted in immune activation in the TME and macrophage infiltration. The combination of LV plus pembrolizumab resulted in a more potent immune activation in the TME and a prominent influx of CD8 T cells in addition to macrophages. Together these results provide a rationale for the continued clinical investigation of LV alone or in combination with pembrolizumab. Trial Registration: NCT01969643 and NCT03310957 Ethics Approval: The study protocols for clinical trials represented in this publication were reviewed by the respective IRB/IEC at each study site and approved before trial participants were screened and enrolled. Consent: Not applicable.